The need for integrated an approach in confronting snakebite envenoming in Latin America: The relevance of endogenous scientific and technological research - GUTIÉRREZ, José María; PEREAÑEZ, Jaime Andrés (Vitae, 2016)
Snakebite envenomings constitute a serious public health problem on a global level, especially in Africa, Asia and Latin America. In our Latin American region, it is estimated that at least 70,000 snakebite cases occur every year, although the actual number is likely to be higher. This pathology is one of the so-called ‘neglected tropical diseases’, i.e. a group of diseases that affect primarily poor people in poor settings and, therefore, does not receive the necessary attention from research agencies, pharmaceutical companies, and health authorities. Consequently, it has been described as a ‘disease of poverty’. In our continent it largely affects impoverished populations living in rural areas, including indigenous groups.